Three essays on corporate finance - He, Zhongda (2014)
The dissertation comprises three essays on corporate finance. In essay one we examine whether corporate boards serve as a substitute or as a complement to external governance, using private firms as a setting for lack of external governance force. Supporting the substitution view that lack of external governance, such as hostile takeovers and stock market monitoring, makes private firms rely more on board monitoring, we find that compared to public firms, private firms have a smaller board, a higher proportion of outside directors, and a lower likelihood of CEO-chairman duality. We further find that private firms’ CEO turnover-performance sensitivity, going-public likelihood, and IPO value increase with the proportion of outside directors.